Plasma glucose concentration 60 min post oral glucose load and risk of type 2 diabetes and cardiovascular disease: Pathophysiological implications. (July 2019) - Abbasi, Fahim; Tern, Paul JW; Reaven, Gerald M
Aim: The aim of this study was to gain insight into the pathophysiological significance of elevated plasma glucose concentrations (mmol/L) 60 min post oral glucose load in apparently healthy individuals. Methods: Comparison of resistance to insulin action and associated cardio-metabolic risk factors in 490 apparently healthy persons, subdivided into those with a plasma glucose concentration 60 min following a 75-g oral glucose challenge of <8.6 versus ⩾8.6. Results: Insulin resistance was significantly greater in persons with normal glucose tolerance whose 60-min glucose concentration was ⩾8.6, associated with higher blood pressure, plasma concentrations of glucose, insulin, triglyceride and lower high-density lipoprotein cholesterol concentrations. Similar differences were seen in persons with impaired fasting glucose, but not in those with impaired glucose tolerance or both impaired fasting glucose and impaired glucose tolerance. The group whose 60-min glucose was <8.6 ( n  = 318) contained primarily persons with normal glucose tolerance (88%), whereas the majority of those whose 60-min value was ⩾8.6 ( n  = 172) had prediabetes (59%) and in particular combined impaired fasting glucose and impaired glucose tolerance. Conclusion: Plasma glucose concentration of ⩾8.6 mmol/L 60 min post oral glucose identifies higher proportions of combined impaired fasting glucose and impaired glucose tolerance individuals as well as normal glucose tolerance and impaired fasting glucose individuals with a more adverse cardio-metabolic profile, contributing to observed increased overall risk of type 2 diabetes and other metabolic diseases.